Analisis Faktor Kesalahan Dalam Proses Pengisian Saldo Kedalam Dompet Digital Yang Dituju Dengan Aplikasi BCA Mobile - Marshal, Aldo Leviko; Fajar, Ahmad Nurul (Metta : Jurnal Ilmu Multidisiplin, 2023)
Digital money has become a modern transaction tool used today in the form of a number of balances for buying and selling transactions. Apart from the ease of making transactions with digital money innovations, it is possible that errors may occur in sending the balance to the intended digital wallet. This research aims to determine the influence of display quality factors, system services, and information service factors in the process of topping up balances into digital wallets. This research method uses a quantitative method by collecting data using a questionnaire by distributing questions using Google Form tools to 200 respondents who use the BCA Mobile application in Indonesia. The research results obtained by carrying out the f square test illustrate that the Visual Quality factor has a very significant impact on errors in topping up balances to digital wallets, then the System services factor also has quite a significant impact on errors in topping up balances to digital wallets, and on the factors Information quality does not have a significant impact on errors in filling in balances to digital wallets.